A New Aluminum Pot Line Rectiformer Scheme with Effective Harmonic Suppression Capability - Mahmood Al-Mahari; S. Ali Al-Mawsawi; Fadhel Albasri (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
The conversion from alternating current to direct current creates harmonics and causes power quality issues especially when large amount of power being converted. To mitigate these issues, conventional schemes for pot line Rectiformers are integrated with passive harmonic filters (PHF), which are either connected directly to the feeding grid or connected to each tertiary winding of the Rectiformer regulating transformer. This paper presents a new pot line Rectiformer scheme that reduces the distortion at the Rectiformer terminal and has better harmonic attenuation capability at the point of common coupling (PCC) by using parallel delta connected (PDC) tertiary winding between two adjacent Rectiformers. The proposed pot line scheme is modeled and simulated using MATLAB/Simulink. A comparison is made with Aluminum Bahrain (ALBA) new 900MW pot line 6 (PL6) scheme in terms of harmonic elimination, capability, operational constrains and cost/space requirements.